Stoicki kontekst użycia przymiotnika ΤΕΛΕΙΟΣ w Mt 5, 48 - Torbus, Sławomir (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2014)
The aim of this text is a critical analysis of the argument proving that the Greek translations introduced to the text of the call made by Jesus to his audience in Matthew 5, 48 is consistent with concepts of Stoic ethics. The analysis will refer to observations already made by researchers up until this point, proposing at the same time that we should look closely at certain elements which eliminate problems of interpretation.
Keywords: New Testament; Gospel of Matthew; Stoicism; rhetoric